School dropout in Kut District (A Study in Population Geography) - Mansoor Srayyh, Mohsin (Journal of College of Education, 2021)
The study aims to address the dropouts from the school in the Kut district and determine their characteristics as well as the characteristics of their families, and the most important reasons affecting the school dropout as well as its negative effects. Primary, intermediate, and preparatory) for the academic year (2018-2019). The study found that the dropout rate for females compared to males is clear in the countryside due to social norms that negatively affected the continuation of female education compared to males, and that dropout increased in the primary stage from the next two stages Intermediate and preparatory, and the study showed that the school dropout is linked to the social and economic factors of the family such as poverty, housing, academic achievement and the guardian’s profession. The study also revealed the danger that threatens the youth category represented by the negative effects of the school dropout, foremost among which are crime, drug addiction, and encouragement towards thefts as well as smoking .